The computer paradigm in vocational guidance - Fogliatto, Hermelinda M. (Orientación y Sociedad.)
The technological advances in last decades have transformed the external resources of Vocational Counseling, Occupational Information and assessment of clients. Most computer systems follow a behaviorist-cognitive approach. However, the use of vocational counseling software is not exclusive to one conceptual approach. Computers are introduced in education from primary school; counselors and other educators are expected to use those systems. The attitude of counselors ranges from enthusiastic acceptance to complete refusal. Many counselors fear that computers will replace them. An underlying theory holds that counseling is based on the counselor-client interaction. A computer- client interaction cannot be considered vocational counseling. Counseling has five basic aims: prevention, assistance, education and development, service of diverse groups and research. The most relevant trends in computer-based counseling are: tests and questionnaires based on computers, adaptive development, computarized information, vocational counseling systems and research. Basic aims and the potential role of computers in achieving them are discussed. Present vocational counselors can use the technology of computers to link the past of our profession to its promising future. In view of these premises we have developed two computer systems that assist the vocational counseling process: "Professional Interests Questionnaire, Computer Version", and "Computer-based System of Vocational Counseling".